Education-Spiritual Care Intervention (ESCI) and self care of community dwelling senior citizens with type 2 diabetes - Rodulfa, Ester R.
The purpose of this study is to generate knowledge on how educational-spiritual care intervention (ESCI) affect diabetes self care activities of community dwelling senior citizens with type 2 diabetes, and to gain insight on the qualities of the intervention that lead to treatment satisfaction. The study utilized a quasi-experimental one group pre test posttest design for the quantitative part and focus group discussion for the qualitative part. It was participated by 33 senior citizens with type 2 diabetes who were seeking consultation at a primary health care center. Findings suggest that that after the intervention, significant improvement in self care activities and spiritual health of senior citizens were observed. Findings further suggest that variables such as family support, having concordant co-morbidities, and the number of clinic visits were associated with the practice of some self care activities. The number of years diagnosed with diabetes however, was not associated with any self care activity. The participants described the qualities of the intervention that gave them treatment satisfaction in themes as being humane, being accessible, being educational, effective, and one that provides social connectedness. Diabetes knowledge and spiritual health leads to improvement in self care practices. Family support that allows seniors to shift role from caregiver to care receiver enhances self care. Increased clinic visits enable ro prescribe blood glucose monitoring and therefore increase the practice of this self-care activity. Co-morbidities that are concordant with diabetes have similar diet regimen can increase the chances of participating of this self care activity. It is not the number of years of diagnosis that affect the practice of self care, but the type of symptoms felt. When symptoms are uncomfortable, patients are more likely to practice self care. Analysis revealed that the qualities of the intervention that result to treatment satisfaction are mostly influenced by good nurse-patient interaction since it is the factor that establishes the kind and the manner of how care is delivered. Educational-spiritual care intervention (ESCI) therefore provides a holistic nursing care which improves the practices of diabetes self care activities, spiritual health and treatment satisfaction of community dwelling senior citizens with type 2 diabetes.